“Minha Casa, meu Trabalho...”: Trabalho Domiciliar na Indústria de Confecções de Goiás - Enoque, Alessandro Gomes (Teoria e Prática em Administração, 2015)
This study has for objective to understand the settings of homework in the city of Jaraguá/GO/Brazil (major hub producer of clothing). In a qualitative study, 15 semi-structured interviews were conducted in the period april to september 2012, treated material through discourse analysis. The survey data suggests an extensive network of subcontracting small "factions" that perform activities (informal) sewing and finishing for various companies in the country. We could also find a picture of poor quality with low wages, unsanitary conditions, long hours and lack of social rights, which reveals a contradictory dynamic of accumulation and wealth by the contractors, and impoverishment and instability in relation to the production process that sustains such organizations.